가속도계를 이용한 탄성파 기반 누수탐지 기술 분석 - 최광묵(Kwangmook Choi); 이호현(Hohyun Lee); 신강욱(Gangwook Shin); 홍성택(Sungtaek Hong) (한국정보통신학회논문지, 2020)
Water pipes are laid on the ground, making it impossible to visually detect leaks due to aging of pipes, and technology to detect leaks in pipes is mainly used to detect leaks in pipes by detecting leaks. In this paper, two accelerometers were attached to both ends of the constant water piping to calculate the time difference between the acquired data to detect leakage points. The leak test of piping was performed by installing valves at 4.3m, 8.6m, and 12.9m points on piping 17.2m, and changing the development rate of valves to 30% and 70%. Leakage can be detected for pressure drop in piping, which is 30% and 70% open valve. It is very important to detect leakage in the early stage, and it is judged that detection of the initial leak point from the algorithm applied in this paper will be possible. 상수도 배관은 땅속에 매설되어 있어서 배관의 노후화에 따른 누수를 맨눈으로 탐지하기가 불가능하며, 누수음을 감지함으로써 배관의 누수를 탐지하는 기술이 주로 사용된다. 본 논문에서는 상수도 배관의 양단에 두 개의 가속도계를 부착·취득한 데이터 간의 도달 시간 차이를 계산하여 누수 지점을 탐지하는 알고리즘을 개발하였다. 배관의 누수 시험은 17.2m의 배관에 4.3m, 8.6m, 12.9m 지점에 밸브를 설치하고, 밸브의 개도율을 30%, 70%로 변경해 가면서 누수 지점을 분석하였으며, 밸브가 30%, 70%씩 개방된 정도의 배관 내 압력 강하에 대해서는 누수를 탐지할 수 있는 것으로 확인되었다. 초기 단계의 누수를 탐지하는 것이 매우 중요하며, 본 연구에서 적용한 알고리즘으로부터 초기의 누수 지점의 탐지가 가능할 것으로 판단된다.